The remarkable, rough-riding life of Theodore Roosevelt and the rise of empire America - Harness, Cheryl (Washington, D.C. : National Geographic, 2007)
Presents the life and accomplishment of the twenth-sixth president, in a period which saw the rise of the United States as a world power.
The Roosevelts of 20th Street -- Coming of age -- The crowded years, 1884-1898 -- Roosevelts in the White House, 1901-1909 -- The rest of his life, 1909-1919.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes bibliographical references (p. 140) and index.
Description based on print version record.
Keywords: Roosevelt, Theodore, -- 1858-1919 -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; United States -- Politics and government -- 1901-1909 -- Juvenile literature; United States -- Foreign relations -- 1901-1909 -- Juvenile literature; United States -- Territorial expansion -- Juvenile literature; Roosevelt, Theodore, -- 1858-1919.; United States -- Politics and government. -- 1901-1909.; Presidents; Electronic books- OSLIS; Electronic books